Hexagonal Prisms Form in Water‐Ice Clouds on Mars, Producing Halo Displays Seen by Perseverance Rover. Issue 17 (9th September 2022) - Lemmon, M. T.; Toledo, D.; Apestigue, V.; Arruego, I.; Wolff, M. J.; Patel, P.; Guzewich, S.; Colaprete, A.; Vicente‐Retortillo, Á.; Tamppari, L.; Montmessin, F.; de la Torre Juarez, M.; et al.
Abstract: Observations by several cameras on the Perseverance rover showed a 22° scattering halo around the Sun over several hours during northern midsummer (solar longitude 142°). Such a halo has not previously been seen beyond Earth. The halo occurred during the aphelion cloud belt season and the cloudiest time yet observed from the Perseverance site. The halo required crystalline water‐ice cloud particles in the form of hexagonal columns large enough for refraction to be significant, at least 11 μm in diameter and length. From a possible 40–50 km altitude, and over the 3.3 hr duration of the halo, particles could have fallen 3–12 km, causing downward transport of water and dust. Halo‐forming clouds are likely rare due to the high supersaturation of water that is required but may be more common in northern subtropical regions during northern midsummer. Plain Language Summary: A scattering halo, or bright ring around the Sun, was seen in pictures taken by cameras on the Perseverance rover. Such halos are commonly seen in ice clouds on Earth but have never before been seen on Mars. When the halo was seen, on 15 December 2021, the rover was within a period of unusually cloudy weather near the end of a season known for water‐ice clouds in northern tropical areas such as the rover's site in Jezero crater. The appearance and size of the halo showed that the clouds were made of water‐ice crystals shaped like hexagonal columns. The crystals were likely larger than those in most water‐ice clouds on Mars, which allowed the halo to form. Key Points: A 22°‐radius halo around the Sun was imaged for over 3 hr by cameras on the Perseverance rover on Mars Such a halo is diagnostic of scattering by large, hexagonal water‐ice crystals and has not previously been seen beyond Earth The halo implies that high supersaturation of water may be more common in late summer in the northern subtropics than elsewhere